(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2022)
The purpose of the study has been to differentiate the importance of the high-performance work systems (HPWS) effects, for dimensions, in the performance of sales representatives of pharmaceutical companies in Chiclayo having affective commitment and human capital as mediation variables. HPWS have a significant effect on development through human capital, but not with affective commitment. However, there are HPWS’ subdimensions that affect development through the “motivational path” (training, performance assessment and empowerment practices) which also affect in a considerable way through human capital. An activity that also affects performance through human capital significantly is the compensations and incentives one.